SGLT2 inhibitors in the treatment of type 2 cardiorenal syndrome: Focus on renal tubules - Wang, Yajiao; Mao, Xinxin; Shi, Shuqing; Xu, Xia; Lv, Jiayu; Zhang, Bingxuan; Wu, Huaqin; Song, Qingqiao (Frontiers in Nephrology, 2023)
Abstract: The pathogenesis of type 2 cardiorenal syndrome (CRS) is mostly associated with reduced cardiac output, increased central venous pressure (CVP), activation of the renin-angiotensin-aldosterone system (RAAS), inflammation, and oxidative stress. As a drug to treat diabetes, sodium-glucose transporter 2 inhibitor (SGLT2i) has been gradually found to have a protective effect on the heart and kidney and has a certain therapeutic effect on CRS. In the process of chronic heart failure (CHF) leading to chronic renal insufficiency, the renal tubular system, as the main functional part of the kidney, is the first to be damaged, but this damage can be reversed. In this review, we focus on the protective mechanisms of SGLT2i targeting renal tubular in the treatment of CRS, including natriuresis and diuresis to relieve renal congestion, attenuate renal tubular fibrosis, improve energy metabolism of renal tubular, and slow tubular inflammation and oxidative stress. This may have beneficial effects on the treatment of CRS and is a direction for future research.